Membangun citra positif melalui public relations untuk meningkatkan minat nasabah pada produk perbankan syariah - Setiawan, Aldika Bayu (Maliki Interdisciplinary Journal, 2024)
This study aims to examine the role of public relations (PR) in building a positive image of Islamic financial institutions and its impact on customer interest in Islamic financing products. A strong positive image can increase customer trust and loyalty, which in turn will have an impact on increasing participation in products offered by Islamic banking. The method used in this research is qualitative analysis, with data collection through literature searches, or what is often referred to as the “library research” method. The results showed that effective PR strategies, such as transparent communication, community engagement, and managing feedback and evaluation to financing customers, contributed significantly to creating a positive image. This study recommends the development of more integrated PR strategies to further increase customer interest and strengthen the position of Islamic financial institutions in the market.